PEMETAAN PENELITIAN ORIENTALIS TERHADAP HADIS MENURUT HARALD MOTZI - Ulummudin (Department of Hadis Sciences (IH), Faculty of Usuluddin, Adab, and Da'wah (FUAD), State Islamic Institute of Langsa (IAIN), 2020)
This paper focuses on maping hadiths studies which has been done by orientalists according to Harald Motzki. So far, the maping is always seen based on an assuption which results three sections namely sceptic, non-sceptic, and middle ground. Unlike prior studies, Motzki tries to divide hadiths studies in the West based on the method they use Based on it, it is obtained a conclusion that hadiths studies in the West are not stagnant and similiar. On the contrary, it undergoes a progress time by the time. Based on the method employed to examine the authenticity of hadiths. The study of hadith in the West can be classified into four divisions. First, is matan which was introduced by Ignaz Goldziher, Josep Schacht, and Marston Speight. Second, is dating based on collections of hadis books with Josep Schacht as a initiator. Third, is dating by isnad which was started by Josep Schacht and Juynboll. Fourth, is isnad-cum-matan which was embarked by Harald Motzki.